Large-scale integration in tablet screens for blue-light reduction with optimized color: The effects on sleep, sleepiness, and ocular parameters. Issue 1 (1st January 2017) - Ayaki, Masahiko; Hattori, Atsuhiko; Maruyama, Yusuke; Tsubota, Kazuo; Negishi, Kazuno
Abstract: We investigated sleep quality and visual symptoms in 30 adults who spent two hours before bedtime using a tablet device with and without the advanced technology of large-scale integration for blue-light reduction and color management. Dry eye- and eye fatigue-related symptom scores were significantly better with than without blue-light reduction. Sleepiness and saliva melatonin during the task were greater with blue-light reduction, however, overnight melatonin secretion and sleep quality parameters were similar in both conditions. In conclusion, tablet devices using large-scale integration for blue-light reduction increased sleepiness and reduced eye fatigue and dryness during tasks before bedtime.